Faster indentation influences skin deformation to reduce tactile discriminability of compliant objects - Li, Bingxu; Hauser, Steven C.; Gerling, Gregory J. (IEEE transactions on haptics, 2023)
To discriminate the compliance of soft objects, we rely upon spatiotemporal cues in the mechanical deformation of the skin. However, we have few direct observations of skin deformation over time, in particular how its response differs with indentation velocities and depths, and thereby helps inform our perceptual judgments. To help fill this gap, we develop a 3D stereo imaging method to observe contact of the skin's surface with transparent, compliant stimuli. Experiments with human-subjects, in passive touch, are conducted with stimuli varying in compliance, indentation depth, velocity, and time duration. The results indicate that contact durations greater than 0.4 s are perceptually discriminable. Moreover, compliant pairs delivered at higher velocities are more difficult to discriminate because they induce smaller differences in deformation. In a detailed quantification of the skin's surface deformation, we find that several, independent cues aid perception. In particular, the rate of change of gross contact area best correlates with discriminability, across indentation velocities and compliances. However, cues associated with skin surface curvature and bulk force are also predictive, for stimuli more and less compliant than skin, respectively. These findings and detailed measurements seek to inform the design of haptic interfaces.